Una vuelta por la plaza: propuesta de serie documental híbrida para la visibilización de la cultura e historia de las plazas de mercado (2022)
The purpose of this degree project is the creation of an audiovisual proposal that allows me to visualize the historical, cultural and symbolic aspects of the Colombian market squares through the development of a documentary series as a contribution to the audiovisual narratives used in Colombia, from the perspective and concepts from the field of graphic design. Applying the narratives of hybrid documentaries, traditions, stories, anecdotes and real events will be followed, which unfold within the market places applied to a fictional context told from the perspective of Colombian families. The development of this degree project focuses on establishing the stage of audiovisual development, for the realization of a teaser and graphics proposals that allow presenting the concepts and ideas proposed for the development of the themes of the hybrid documentary series.